Editorial - BETTY C MUBANGIZI; OLIVER MTAPURI (African Journal of Governance and Development, 2020)
The COVID-19 pandemic has highlighted our failures to deal with unemployment, inequality, poverty, corruption, civil conflict and unrest, and gender equality. We dare say we have abysmally failed to deal with the issue of gender-based violence, which spiked with the emergence of COVID-19. We have seen the unrelenting marginalisation of the subalterns. We have witnessed women's continued oppression under various patriarchal practices that are anathema to the accordance of the value of what women are to society as mothers, sisters, bearers, and bringers of humankind – simply priceless. We draw wisdom from the Shona proverb, 'Kupedza nyota kuenda padziva' which translates - To quench thirst is to go to the stream, and if you need help and information, you should go to an expert or an eyewitness. We are of the view that we have all the information that we need to articulate those lived experiences; the experts are there; the knowledge and know-how are explicit in the communities we live in - the episteme, the ontologies, the theories abound in our communities. We must learn, write, document, preserve, and curate them – that is the challenge we are putting forward to you as African scholars and all contributors to this journal.